KEPEMILIKAN INSTITUSIONAL DAN KUALITAS AUDIT TERHADAP PENGUNGKAPAN INFORMASI DAN FUTURE EARNINGS RESPONSE COEFFICIENT - Etty Murwaningsari (University of Merdeka Malang, 2014)
The objectives of this research were to analyze the direct effects of institutional ownership and audit qualitytowards future earnings response coefficient, as well as their indirect effects towards future earnings responsecoefficient through disclosure as intervening variable. This research used secondary data from manufacturingcompanies listed in Indonesia Stock Exchange (IDX) between 2002-2011. The number of samples used in thisresearch were 111companies. The method used in this research was Structure Equation Model (SEM) processedusing AMOS 6. The results of this research demonstrated that institutional ownership and disclosure hadpositive significant effect while audit quality had negative significant effects towards future earnings responsecoefficient. On the other hand, institutional ownership had positive significant effect while audit quality hadnegative significant effects towards disclosure. Further testing proved that indirect effect was very weak.Control variable which had positive significant effect was profitability towards disclosure while leverage andlong term investment had negative significant towards future earnings response coefficient. Liquidity variableswere proven that they had no effect towards disclosure.